2009
DOI: 10.1007/s11250-009-9381-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal parasites of working donkeys of Ethiopia

Abstract: The general prevalence and population composition of gastrointestinal and pulmonary helminths of working donkeys were studied. For the purpose 2935 working donkeys were coprologically examined for nematode and cestode, and 215 donkeys for trematode infections. Seven donkeys that died due to various health problems or were euthanased on a welfare ground were necropsied and the parasites were recovered and identified to the species level. The study was conducted during the periods 1996-1999.Coprological examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
61
11
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 14 publications
14
61
11
1
Order By: Relevance
“…This is in agreement with the work of Ayele et al [23], who reported 3% and Getachew et al [27] who reported 2% in donkeys. Study conducted in Western highlands of Oromia, Ethiopia indicated 2.1% prevalence of Oxyuris equi in horses [11].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is in agreement with the work of Ayele et al [23], who reported 3% and Getachew et al [27] who reported 2% in donkeys. Study conducted in Western highlands of Oromia, Ethiopia indicated 2.1% prevalence of Oxyuris equi in horses [11].…”
Section: Discussionsupporting
confidence: 94%
“…The prevalence of Strongyles infestation was 87.81% in donkeys. Similar studies conducted in different parts Ethiopia indicated higher prevalence than the current study with an overall prevalence of 99%, 100%, 100%, 98.2% and 100% in Ada, Akaki Boset [27], Dugda Bora distinct [23], highlands of Wollo province [22], Western highlands of Oromia [11] and Wonchi [21], respectively.…”
Section: Discussionsupporting
confidence: 83%
“…Las moscas del género Gasterophilus, comprenden ocho especies en todo el mundo 35 , con reportes de prevalencias que varían entre el 3 y 94% 19,24,36 , sin embargo, las especies de Gasterophilus tienen diferente distribución en el mundo aunque solamente Gasterophilus intestinalis y Gasterophilus nasalis presentan distribución mundial 21,23,38,46 , es así como, sólo dos de estas especies (G. nasalis y G. intestinalis) han sido las reportadas en Argentina 11 y Chile 44 .…”
Section: Introductionunclassified
“…Getachew et al (2010) reported that many helminth species are found in these animals and cause direct damage to their health. Nevertheless, there are insufficient studies with data on strategic control of gastrointestinal helminthic parasites that affect this equine species (MATTHEE et al, 2002;VENEZIANO et al, 2011 infection between the ages of 15 and 23 weeks (SOULSBY, 1982), animals older than six months may still acquire the infection, such that 30% of them are infected (WELLS et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Getachew et al (2010) reported that many helminth species are found in these animals and cause direct damage to their health. Nevertheless, there are insufficient studies with data on strategic control of gastrointestinal helminthic parasites that affect this equine species (MATTHEE et al, 2002;VENEZIANO et al, 2011).…”
Section: Introductionmentioning
confidence: 99%